Ice rubble attenuation of ice loads on arctic offshore structures - Wong, T. T.; Morgenstern, N. R.; Segoz, D. C. (Canadian Geotechnical Journal, 1991)
A state of the art survey of ice rubble mechanics is first presented. This survey covers ice rubble morphology, laboratory testing of ice rubble, the study of the load transmission capability of existing rubble fields, and field measurements in ice rubble surrounding offshore structures. Then, the implementation of a new plasticity model for normally consolidated broken ice into an existing finite element stress analysis code is described. The resulting program is validated using triaxial test data. Using this model, a two-dimensional parametric study on ice force transmission through a grounded ice rubble field is performed. The study shows that, in addition to the mechanical properties of ice rubble, the island or berm geometry may significantly affect the ice load. Key words: constitutive model, finite element analysis, ice load, ice rubble, offshore structure, plasticity.